An investigation on condom uptake among commercial sex workers in Jacha Epworth Zimbabwe - Maarira, Lindiwe Loice (Midlands State University, 2018)
The study was designed to investigate condom uptake among prostitutes in Jacha. The study attempted to fulfil the following objectives: ascertain what condoms are, establish the benefits or importance of using condoms, identify strategies to promote condom accessibility and acceptability in Jacha as well as ascertain who initiated condom use between sex workers and their clients. The rationale of this study lay in the fact that condoms have been proven to significantly prevent unwanted pregnancies, sexually transmitted infections and HIV but uptake of these protective devices is inconsistent even in risky sexual encounters. The study used the descriptive research design. Data were collected using a questionnaire and interview schedule. The data were collected from 200 respondants who were sampled using the random sampling technique. It was hoped that the results of the study would be generalised to the population of Jacha and interventions to promote condom uptake be implemented as recommended. The respondants knew what condoms were and what the condoms protective functions were but the majority cited inconsistent condom use due to a number of factors such as being offered more money for unprotected sex.It was also established in the course of the study that the respondants of either sex had difficulties in negotiating for safe sex.The female respondants cited fear of violent clients and competition among the sex workers while the male respondants cited patriarchal reasons for their inability to negotiate for condom use. Further research was recommended to reveal the determinants of low condom uptake and how they can be eradicated. Promoting condom use was also recommended with the Ministry of Health and local nurses at the forefront. It was also recommended that the government through the Ministry of Health construct a clinic to cater for the sexual and reproductive health needs of the sex workers in Jacha.